Comparison of two anorganic bovine bone in maxillary sinus lift: a split-mouth study with clinical, radiographical, and histomorphometrical analysis - Heitor Fontes da Silva; Douglas Rangel Goulart; Alexander Tadeu Sverzut; Sergio Olate; Márcio de Moraes (SpringerOpen, 2020)
Abstract Background Anorganic bovine bone (Bio-Oss®) has been extensively used for reconstruction of posterior area of maxilla in sinus lift procedure; however, a new graft material (Lumina-Bone Porous®), that has a different manufacturing process, has not been yet compared in clinical and histological terms. The manufacturing process of bovine bone graft is related to size and porosity of the particles, and this can change osteoconductive property of the material and bone formation. The use of Lumina-Porus® could improve bone formation, reduce the remaining particles of the biomaterial using a low-cost material. The aim of this research was to compare the clinical, radiological, and histomorphometrical results from maxillary sinus lift with two different anorganic bovine bone substitutes Bio-Oss® (control) and Lumina-Bone Porous® (test). Results A split-mouth study was performed with 13 volunteers. The mean bone ridge height in the deepest portion of maxillary sinuses floor was 3.11 ± 0.83 mm in the Bio-Oss® and 2.38 ± 0.75 mm in the Lumina-Bone Porous®. After sinus lift, the Bio-Oss® group shows bone ridge height of 11.56 ± 2.03 mm and Lumina-Bone® of 10.62 ± 1.93 mm. The increase in alveolar bone height scores was significant between pre-augmentation and 6 months after SL in both groups (p < 0.001). No statistical significant difference in newly formed bone in the Bio-Oss® group (20.4 ± 5.4%), and Lumina-Bone Porous® (22.8 ± 8.5%) was histomorphological observed (p > 0.05). On the other hand, the residual graft particles showed significant difference between the Bio-Oss® group (19.9 ± 8.6%) and Lumina-Bone Porous® (14.6 ± 5.6%) (p < 0.05). The survival rate of dental implants for augmented area with Lumina Bone Porous® was 88.88%, while for Bio-Oss® group was 100%. Conclusion Both materials Bio-Oss® and Lumina-Bone Porous® can be used in the maxillary sinus floor augmentation with good predictability in clinical, radiographical, and histological point of view.